Gene therapy for renal diseases and transplantation - Benigni, Ariela; Remuzzi, Giuseppe 1949- (Contributions to nephrology, 2008)
Initially conceived as a strategy to remedy inherited genetic disorders, gene therapy has been successfully applied in the last decade to ameliorate the renal function compromised by progressive renal diseases and to prevent kidney allograft rejection in experimental animals.In the present book, world-renowned experts are presenting new insights into viral and non-viral systems used to effect gene delivery, one chapter being dedicated to the new field of RNA interference (RNAi). This latter method may be successfully used in renal ischemia-reperfusion injury, trauma and transplantation. In the near future, gene therapy might also prove to be a new strategy to target molecules involved in tissue damage and inflammation processes that underlie ARF. So far, gene transfer has been successfully applied in experimental glomerulonephritis and interstitial fibrosis, and studies in larger animals are keenly awaited. Also covered are issues related to transplantation, which is the therapy of choice in many end-stage organ failures. Transfer of genes whose protein products have immunomodulatory properties have proven beneficial in treating acute and chronic graft rejection, one of the problems not satisfactorily solved by current anti-rejection drugs. Gene therapy thus may become a reality in clinical transplantation once its efficacy in larger animals has been demonstrated. Last but not least, a possible benefit of targeted gene therapy in renal cancer or HIV-associated nephropathy is explored.Covering a wide spectrum of topics, this publication provides a valuable overview of current developments and issues